Serum levels of organochlorine pesticides and polychlorinated biphenyls among inhabitants of Greater Metropolitan Rio de Janeiro, Brazil Níveis séricos de pesticidas organoclorados e bifenilos policlorados em habitantes da Área Metropolitana do Rio de Janeiro, Brasil - Isabella Fernandes Delgado; Heloisa H.C. Barretto; Teresa A. Kussumi; Irene Baptista Alleluia; Cenira de A. Baggio; Francisco José Roma Paumgartten (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
Levels of persistent organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were determined in the blood serum of people living and working in the urban area of greater Rio de Janeiro city. Blood samples from 33 volunteers (16 males, 17 females, 19-63 years old) were taken in January 1999. OCP residues (op'DDT, pp'DDT, pp'DDD, pp'DDE, Aldrin, Dieldrin, Endrin, Heptachlor, Heptachlor-epoxide, alpha-, beta- and gamma-Hexachlorocyclo-hexane, Hexachlorobenzene) and PCBs (congeners: 28, 52, 101, 138, 153, 180) were extracted with n-hexane and analyzed by gas chromatography with electron capture detection. Except for pp'DDE (detection limit = 1.4µg/L) no other OCP residue was found in the samples. No PCB congener (detection limit = 2.0µg/L) was detected either. pp'DDE was found in 17 out of 33 samples in concentrations that ranged from 1.4 to 8.4 µg/L of serum or, on a fat basis, from 0.200 to 3.452 µg/g of serum lipids. Percentage of positive samples (%) and levels of pp'DDE (range of positive samples) increased from the youngest to the oldest group (<=29 yrs: 10%, 0.278µg/g; 30-39 yrs: 60%, 0.200-0.765µg/g; > or = 40 yrs: 77%, 0.257-3.452µg/g). Os níveis de pesticidas organoclorados persistentes (POPs) e de bifenilos policlorados (PCBs) foram determinados no soro sangüíneo de pessoas que vivem e trabalham na área urbana do grande Rio de Janeiro. Amostras de sangue foram coletadas de 33 voluntários (16 homens, 17 mulheres, idade: 19-63 anos) em Janeiro de 1999. Resíduos de POPs (op'DDT, pp'DDT, pp'DDD, pp'DDE, Aldrim, Dieldrim, Endrim, Heptacloro, Heptacloro-epóxido, alfa-, beta- and gama-Hexaclorociclo-hexano, Hexaclorobenzeno) e PCBs (congeneres: 28, 52, 101, 138, 153, 180) foram extraídos com n-hexano e analisados em cromatógrafo gasoso com detector de captura de elétrons. Com exceção do pp'DDE (limite de detecção =1,4µg/L), não foram encontrados outros resíduos de POPs nas amostras. Não foram encontrados também, congêneres de PCBs (limite de detecção = 2,0µg/L). O pp'DDE foi encontrado em 17 das 33 amostras em concentrações que variavam de 1,4 a 8,4 µg/L de soro ou, em termos da gordura, de 0,200 a 3,452 µg/g de lipídios séricos. A percentagem de amostras positivas (%) e os níveis de pp'DDE (intervalo de concentrações das amostras positivas) aumentaram do grupo etário mais jovem para o mais idoso (<=29 anos: 10%, 0,278µg/g; 30-39 anos: 60%, 0,200-0,765µg/g; > ou = 40 anos: 77%, 0,257-3,452µg/g).